Synthetic Reconstruction of the Carpal Short Radial Collateral Ligament Following a Partial Sprain Injury in a Dog - Dekerle, Bastien; de Gail, Péroline; Crumière, Antonin; Goin, Bastien (VCOT Open, 2025)
This study aims to report the clinical presentation, diagnosis, surgical treatment, and follow-up of a chronic traumatic grade 2 sprain of the carpus involving partial rupture of the short radial collateral ligament (SRCL) in a dog. A 5-year-old, 25-kg spayed female crossbreed dog was diagnosed with a traumatic grade 2 sprain injury of the SRCL of the left carpus. Despite carpal splinting for 1 month, persistent lameness warranted surgical reconstruction. It was achieved using a single synthetic ultra-high-molecular-weight polyethylene implant, going from the radius into the intermedioradial bone and around the second metacarpal bone to reconstruct the two strands of the SRCL. The reconstruction was stabilized using interference screws and a cortical button. After 1 month of carpal immobilization with a modified Robert Jones, gradual resumption of activity was initiated. At two postoperative months, only grade 1 lameness was present and progressively resolved. One year after surgery, the dog had regained full function without recurrence of lameness on the operated limb. Reconstruction of the SRCL following a traumatic grade 2 carpal sprain in dogs is possible using a braided ultra-high-molecular-weight polyethylene implant secured with interference screws and a cortical button. Despite secondary ankylosis, this technique avoids the use of salvage procedures such as carpal arthrodesis.
Keywords: collateral ligament; radius; dog; synthetic reconstruction; UHMWPE implant